GOLD NETTING TO STRENGTHEN FINANCIAL SYSTEM STABILITY - Meera, Ahamed Kameel Mydin (Journal of Islamic Monetary Economics and Finance, 2017)
Economic and financial crises seem to occur with increased frequency. Indeed now most countries, including several advanced economies like the US, Europe and Japan, are in serious economic recession. Employment and business opportunities have been much dampened. Inflation seems to be soaring globally and nations are witnessing widening gaps in income and wealth distribution. Many of these advanced economies are also facing shrinking population sizes that translate into aging problems and labor shortages. On top of those, there are environmental issues, including global warming. All these, in turn, have caused regional and global political conflicts and turmoil. The Arab Spring and the sovereign debt problems faced by some European countries like Greece are examples of this. Sustainability of economics and environment is thus of paramount concern of today. This paper considers those problems and suggests Interest-free Gold-based Electronic Netting System (IGENS) as an effective way of injecting liquidity into the economy, practically free, that can spur business and employment while bringing about structural stability, inflation checked with both economic and environmental sustainability. Netting or muqassah is a transaction allowed in shari’ah and is practiced worldwide in different forms. Examples include the highly successful WIR Bank of Switzerland, various Local Exchange Trading Schemes (LETS) and Bilateral and Multilateral Payment Arrangements between central banks.